Paracetamol Use During Pregnancy—A Call for Precautionary Action. Issue 3 (March 2022) - Bauer, Ann Z.; Swan, Shanna H.; Kriebel, David; Liew, Zeyan; Taylor, Hugh S.; Bornehag, Carl-Gustaf; Andrade, Anderson M.; Olsen, Jørn; Jensen, Rigmor H.; Mitchell, Rod T.; Skakkebaek, Niels E.; Jégou, Bernard; et al.
Abstract : (Abstracted from Nat Rev Endocrinol 2021;17:757–766) Paracetamol, otherwise known as acetaminophen, is the active ingredient in over 600 prescription and nonprescription analgesic and antipyretic medications. Worldwide and in the United States, more than 50% and 65% of pregnant women use acetaminophen, respectively.